Virulencia, producción y desplazamiento de nematodos entomopatógenos sobre larvas del picudo de la guayaba Conotrachelus psidii Marshall (Coleoptera: Curculionidae) en laboratorio. (2012)
The guava weevil Conotrachelus psidii Marshall is a major pest affecting guava cultivation in Santander, Colombia; it causes serious losses in the quality and the volume of fruit produced. Biological control is a viable option for pest management; entomopathogenic nematodes (EPNs), particularly, have shown good results (63-90% mortality) in controlling fourth instar larvae of the guava weevil. In this study we evaluated the effect of seven species of EPNs isolated in Colombia: Steinernema websteri JCL006, Steinernema sp. 1 JCL024, Steinernema sp. 2 JCL007, Steinernema sp. 3 JCL027, S. colombiense SNI0198, Heterorhabditis bacteriophora HNI0100 and Heterorhabditis sp. SL0708 on fourth instar larvae of the guava weevil in laboratory conditions, and measured the production and the displacement of the most virulent. Heterorhabditis sp. SL0708 induced mortality of 85%, Steinernema sp. 1 JCL024 75% and S. colombiense SNI0198 55%, the other species of EPNs, less than 25% mortality. Increased production of JI by weevil larva was recorded in Heterorhabditis sp. SL0708, which also showed greater recognition capability when the host was C. psidii.